Selection of a MCF-7 Breast Cancer Cell Subpopulation with High Sensitivity to IL-1β: Characterization of and Correlation between Morphological and Molecular Changes Leading to Increased Invasiveness - Eloy Andres Pérez-Yépez; Jorge-Tonatiuh Ayala-Sumuano; Alicia Maria Reveles-Espinoza; Isaura Meza (International Journal of Breast Cancer)
Cancer and inflammation are closely related in tumor malignancy prognosis. Breast cancer MCF-7 cells have a poor invasive phenotype, although, under IL-1β stimulus, acquire invasive features. Cell response heterogeneity has precluded precise evaluation of the malignant transition. MCF-7A3 cells were selected for high sensitivity to IL-1β stimulus, uniform expression of CXCR4, and stability of IL1-RI. Structural changes, colony formation ability, proliferation rate, chemotaxis, Matrigel invasion, E-cadherin mRNA expression and protein localization were determined in these cells and in MCF-7 parental cells under the stimulus of IL-1β. Selected MCF-7A3 cells showed a uniform response to IL-1β stimulation increasing features of invasive cells such as scattering, colony formation, proliferation, chemokinesis and invasion. Basal expression of E-cadherin mRNA was higher, and IL-1β stimulus had no further effect at early times of cytokine exposure. Total E-cadherin levels remained unchanged in parental cells, whereas levels decreased, as MCF-7A3 cells became fibroblastoid or scattered. Triton X-100 soluble/insoluble E-cadherin ratios were highly increased in these cells, while, in MCF-7pl cells, ratios could not be correlated with morphology changes. MCF-7A3 cells uniform response to IL-1β allowed characterization of changes induced by the cytokine that had not been assessed when using heterogeneous cell lines.